Factors Affecting the Teaching of English Syllables and Stress - Benjamin F.C. Nwokedi (MultiTech Publisher, 2023)
The teaching and learning of English syllables and stress are intricate processes influenced by a myriad of factors. This discussion explores significant determinants including linguistic background of learners, teacher competency and training, availability and quality of instructional materials, and learner motivation and attitude towards English pronunciation. The interference from mother tongue and familiarity with phonetic symbols play pivotal roles in how learners grasp phonological aspects of English. Similarly, teacher competency in phonology and pronunciation pedagogy, alongside the ability to model correct pronunciation, significantly impacts the effectiveness of instruction. The quality and cultural relevance of instructional materials, coupled with the integration of modern educational technology, enhance the teaching and learning experience. Moreover, learners' motivation and attitude towards English pronunciation are intertwined with their learning outcomes, underscoring the importance of fostering positive attitudes and high motivation. An integrated approach considering all these factors, supported by continuous professional development for teachers and a well-designed curriculum, is recommended to address the challenges associated with teaching and learning English syllables and stress. Through this holistic approach, a conducive learning environment promoting better understanding and mastery of English pronunciation can be established, ultimately improving the overall language proficiency of learners.